2011
DOI: 10.1186/1479-5876-9-193
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of Dickkopf-related protein 3 in seminal plasma of prostate cancer patients

Abstract: BackgroundExpression of Dkk-3, a secreted putative tumor suppressor, is altered in age-related proliferative disorders of the human prostate. We now investigated the suitability of Dkk-3 as a diagnostic biomarker for prostate cancer (PCa) in seminal plasma (SP).MethodsSP samples were obtained from 81 patients prior to TRUS-guided prostate biopsies on the basis of elevated serum prostate-specific antigen (PSA; > 4 ng/mL) levels and/or abnormal digital rectal examination. A sensitive indirect immunoenzymometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…To date, the exact role of Wnt signaling in prostate cancer progression has remained controversial. The observations that various Wnt antagonists like members of the Dickkopf (Dkk) family are highly expressed in osteotropic prostate cancer cells [ 33 ], upregulated in prostate cancer patients [ 34 ] and that stable expression of Dkk-1 stimulates prostate cancer growth [ 35 ] all suggest that decreased Wnt signaling may also be beneficial for metastatic outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the exact role of Wnt signaling in prostate cancer progression has remained controversial. The observations that various Wnt antagonists like members of the Dickkopf (Dkk) family are highly expressed in osteotropic prostate cancer cells [ 33 ], upregulated in prostate cancer patients [ 34 ] and that stable expression of Dkk-1 stimulates prostate cancer growth [ 35 ] all suggest that decreased Wnt signaling may also be beneficial for metastatic outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal prostate, Dkk-3 is predominantly expressed in the epithelial compartment, whereas in the diseased prostate, Dkk-3 is reduced in the epithelial but elevated in the stromal compartment, especially endothelial cells 1 . We recently demonstrated that in patients with PCa seminal plasma Dkk-3 levels are significantly elevated 2 despite the reduced expression of Dkk-3 in secretory epithelial cells 1 , 3 indicating that Dkk-3 derived from tumor neovasculature/stroma is able to diffuse through the diseased tissue into the prostatic fluid while in normal/BPH tissue an intact basement membrane prevents leakage from the stroma to the epithelial compartment and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, one epidemiological investigation between DKK3 and prostate cancer have been reported. Zenzmaier et al reported that DKK3 levels in seminal plasma were significantly elevated in biopsy-confirmed prostate cancer patients, because loss of expression seems to be counterbalanced by upregulation of DKK3 expression ( 31 ). In this study, we epidemiologically investigated whether SNPs of the DKK3 gene were related to the risk and aggressiveness of prostate cancer for the first time.…”
Section: Discussionmentioning
confidence: 99%